THE CONTRIBUTIONS OF RURAL CREDIT - Nascimento, Marcelo; Pizzaia Ennes , Luiz Gustavo (Revista Interface Tecnológica, 2021)
This research aims to present the contributions of the Rural Credit to family farmers producing Lemon. To achieve the objectives, bibliographic searches were carried out on scientific articles, books and collections. The research has a descriptive-exploratory character and qualitative nature with the aim of being used as a basis for possible debates and discussions on the subject. Even in the face of the serious pandemic scenario of COVID-19, Brazil continues to experience a great increase in the agricultural scenario, thus it becomes clear the need for more comprehensive rural credit lines, aiming at funding and cultural treatments for the production of lemon where the production takes place by a high number of producers who work with family farming. These can also be served by PRONAF (National Program for the Strengthening of Family Farming), the program meets financing for funding and investments in implantation, expansion or modernization of the structure of production, processing, industrialization and services in rural establishments or in areas rural communities, aiming at generating income and improving the use of family labor.
Keywords: Rural Credit; Family farming; Lemon producers; PRONAF